SOME PROBLEMS OF APPEALS OF COURT DECISIONS IN CASES ARISING FROM TAX LEGAL RELATIONS - Євсікова, Олена Віталіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article characteristic features and problems of statutory appeal of court decisions open up in cases, arising from tax jural relationships, on the basis of analysis of current administrative-judicial legislation of Ukraine, and also analysis of judicial practice.